THE WINGS OF THE DOVE: A BRIEF STUDY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2020)
The Wings of the Dove (1902) is the most personal of the famous three novels of Henry James' later phase. The image of the central character in the novel had been in the writer's mind for a long time based as it was on the fond memories of his beloved cousin, Minny Temple.